Representasi Identitas, Penindasan, dan Perlawanan dalam Puisi Bitaqat Huwiyyah Karya Mahmoud Darwis - Nur Amalia Muthmainah; Khomisah Khomisah; Muhammad Nurhasan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
This research focuses on how identity, oppression, and resistance are depicted in the poem Biṭāqat Huwiyyah (Identity Card) written by Mahmoud Darwish, utilizing Alan Swingewood’s sociological perspective on literature. The poem was chosen for its portrayal of the lived experiences of the Palestinian community affected by conflict, occupation, and identity issues. The aim of the study is to explore how the social context and conditions, along with the author’s perspective, contribute to the poem's meaning and to uncover the different representations of identity, oppression, and resistance found within it. The study uses a descriptive qualitative approach, gathering data through library research and notetaking. The main data includes verses from the poem that illustrate themes of identity, oppression, and resistance. Findings indicate that identity is showcased in the poem through the acknowledgment of Arab-Palestinian identity, emotional bonds to the homeland, and shared historical consciousness. Oppression is depicted through the seizure of land, socio-economic exclusion, and bureaucratic control over personal identity. In contrast, resistance is conveyed through the use of language, symbols, and emotional expressions that challenge occupation and the negation of national identity. Thus, this research helps sociology of literature studies grow by illustrating how identity, oppression, and resistance are shown in the conversation between the author's viewpoint, the social context, and the text. Moreover, it broadens the scope of earlier research on Biṭāqat Huwiyyah, which has mainly concentrate on semiotic and linguistic aspects.